Molekulární aspekty nádorů štítné žlázy se zaměřením na mikroRNA a jejich klinické souvislosti - Ludvíková, M; Kholová, I; Kalfeřt, D (Klinicka onkologie, 2017)
BACKGROUND: Central to neoplastic transformation and tumor progression is alteration of the signaling pathways that control cell proliferation and apoptosis. The key mechanisms for this neoplastic process are genetic changes (mutations of cancer-related genes) and recently identified epigenetic changes that involve DNA methylation, chromatin remodeling (which has a profound effect on the control of gene expression), and noncoding, regulatory RNA (notably, microRNA - miRNA). MiRNAs control expression of their target gene post-transcriptionally. These molecular factors have potential as diagnostic, prognostic, and predictive molecular markers. Epithelial tumors of the thyroid gland are a histogenetically, morphologically, and pathobiologically heterogeneous group of neoplasms and require new, molecular approaches in clinical practice. AIM: This review aims to present contemporary scientific knowledge of this molecular (genetic and epigenetic) field of sporadic thyroid tumors of follicular cell origin and their potential clinical implications. The fundamental mutations (BRAFV600E, RET/PTC, RAS, and PAX8-PPARG) in selected tumor types are described comprehensively. Special attention is paid to miRNAs, including their biogenesis, function, and expression profiles in the most common thyroid tumors - follicular adenoma, follicular carcinoma, and papillary carcinoma. CONCLUSION: Thyroid cancer medicine has recently entered a new, molecular era. Comprehensive knowledge of all molecular aspects may improve diagnostics and management of thyroid neoplasms through the introduction of novel, progressive treatment strategies for this cancer. Further research on signaling pathway-related targets, standardization of methods, and evaluation of results are required.Key words: thyroid tumors - cancerogenesis - genetics - epigenetics - microRNA The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 19. 10. 2016Accepted: 2. 11. 2016.
Keywords: Cell Transformation, Neoplastic; signální transdukce; Signal Transduction; nádory štítné žlázy; mikro RNA; Thyroid Neoplasms; Humans; lidé; nádorová transformace buněk; MicroRNAs